Sonographically measured suprailiac adipose tissue is a useful predictor of non‐alcoholic fatty liver disease in obese children and adolescents. Issue 4 (24th September 2014) - Schlieske, C.; Denzer, C.; Wabitsch, M.; Oeztuerk, S.; Mason, R. A.; Thiere, D.; Kratzer, W.
Summary Objective The objective of the present study was to identify ultrasonographic and anthropometric parameters that are highly associated with the presence of non‐alcoholic fatty liver disease (NAFLD) in overweight children and adolescents. Methods A total of 447 overweight children and adolescents (body mass index, 32.4 ± 5.2 kg m−2; mean age, 14.2 ± 1.9 years; range 10.1–20.3 years) were analysed. Subjects underwent ultrasound examination of the liver as well as ultrasonographic measurement of the amount of adipose tissue overlying the biceps brachii and triceps brachii muscles, and of subscapular, suprailiac and abdominal subcutaneous adipose tissue and intra‐abdominal depth. Anthropometric parameters such as body mass index, waist and hip circumference were documented. Results The prevalence of NAFLD was 27.1%; it was significantly associated with the above‐cited anthropometric parameters (P < 0.001). Ultrasonographic findings identified a significant association between NAFLD and the amount of subscapular, suprailiac and abdominal subcutaneous adipose tissue (P < 0.001) as well as between NAFLD and intra‐abdominal depth (P < 0.001). Stepwise logistic regression analysis showed only intra‐abdominal depth for both gender and the deposit of subcutaneous suprailiac adipose tissue in females to be independent predictors of NAFLD. Conclusions In overweight children and adolescents, we identified intra‐abdominal depth for both gender and the ultrasonographically easily determined subcutaneous suprailiac adipose tissue in females as independent predictor of NAFLD.